Сучасні шляхи зниження рівнів професійної патології у робітників, які підлягають впливу локальної вібрації - Андронов, В. А.; Бухман, О. М. (НТУ "ХПІ", 2014)
У статті, що є аналізом сучасної наукової та патентної літератури, розглянуто стан питання щодо негативного впливу виробничої локальної вібрації механічних ручних інструментів на рівень професійної захворюваності робітників. Визначені шкідливі фактори, які мають сумісну дію та посилюють негативний вплив локальної вібрації. Показано, що використання вібропоглинаючих мастик на основі епоксидних смол та олігомерів для зниження локальної вібрації ПРІУД методом нанесення на руків’я є перспективним, доцільним та обгрутованим.

Upon analysis of the available scientific and patent literature it becomes evident that the use of vibration-absorbing mastic (based on epoxy resins and oligomers) in order to reduce local vibration by applying to the handle of a tool is a promising, feasible and reasonable approach. It provides an opportunity to reduce the intensity of local vibration at the point of a contact with a worker (the handle of the tool) and in turn to reduce the likelihood of the occupational conditions development, called «vibration disease». The use of resin-based polymers is also able to reduce the direct impact of low temperature on the hands of a worker, which is a well-known additional factor enhancing the negative impact of vibration. This happens due to mechanical vibrational energy conversion into heat in the coating.
Modern approaches to occupational diseases inceidence reduction in workers dealing with local vibration
Keywords: ручний механізований інструмент; вібраційна патологія; вібробезпека; pneumatic hand tool; local vibration; vibration disease; vibration safety; vibration hazard